An Evaluation of Marginal Fit and Aesthetics in FPD Is Achieved During Graduate Training - M. P. Induja1 , Suresh V2 , Surendar S3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background : The survival of fpd depends on the state of the marginal adaptation.The longevity of fpddepends on the condition of marginal fit and esthetics is also major concern during restoration of anteriorpartial edentulous areas.Hence, adequate marginal fit and esthetics is a goal of a conscientious prosthodontists.The aim of this study is to evaluate the marginal fit and aesthetics in fpd, achieved during graduate training.Materials and methods : A Retrospective study was conducted using the records of the patients. 3178 casesheets were reviewed which were dated between june 2019 to march 2020.the data was collected by thepatient records of saveetha dental college and hospitals.Results: The total sample size of this study was 603,in which 4.3% were 3rd years, 40.1% were 4th years and 55.5% were interns. Tables were distributed basedon USPHS criteria in which Marginal adaptation were smooth margin 63.3%, all margins closed 26.5% andobvious crevice at margin 10%.Based on Colour match, very good colour match were 33% ,good colourmatch were 54% , slightly mismatch of colour were 10% , obvious mismatch were 1% and gross mismatchwere 0.2%. Conclusion : Therefore from this study, we observed that better Marginal adaptation and Colourmatch in fpd was achieved by the interns and the most frequent anatomical site was upper anterior teeth.